(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the improvement of lending practices for manufacturing enterprises in commercial banks through innovation-based approaches.